Analgesic Effects of Hydromorphone versus Buprenorphine in Buprenorphine-maintained Individuals. (January 2019) - Huhn, Andrew S.; Strain, Eric C.; Bigelow, George E.; Smith, Michael T.; Edwards, Robert R.; Tompkins, D. Andrew
Editor's Perspective: What We Already Know about This Topic: The prevalence of patients prescribed buprenorphine for treatment of opioid use disorder is increasing Managing acute pain in buprenorphine-maintained individuals can be challenging What This Article Tells Us That Is New: Large doses of intravenous hydromorphone can provide analgesia in buprenorphine-maintained individuals However, the use of hydromorphone for analgesia in buprenorphine-maintained individuals confers greater abuse liability and side effects than does supplemental intravenous buprenorphine Background: Managing acute pain in buprenorphine-maintained individuals in emergency or perioperative settings is a significant challenge. This study compared analgesic and abuse liability effects of adjunct hydromorphone and buprenorphine using quantitative sensory testing, a model of acute clinical pain, in persons maintained on 12 to 16 mg sublingual buprenorphine/naloxone. Methods: Participants (N = 13) were enrolled in a randomized within-subject, double-blind, placebo-controlled three-session experiment. Each session used a cumulative dosing design with four IV injections (4, 4, 8, and 16 mg of hydromorphone or 4, 4, 8, and 16 mg of buprenorphine); quantitative sensory testing and abuse liability assessments were measured at baseline and after each injection. The primary analgesia outcome was change from baseline cold pressor testing; secondary outcomes included thermal and pressure pain testing, as well as subjective drug effects and adverse events. Results: A significant two-way interaction between study drug condition and dose was exhibited in cold pressor threshold (F10, 110 = 2.14, P = 0.027) and tolerance (F10, 110 = 2.69, P = 0.006). Compared to after placebo, participants displayed increased cold pressor threshold from baseline after cumulative doses of 32 mg of IV hydromorphone (means ± SD) (10 ± 14 s, P = 0.035) and 32 mg of buprenorphine (3 ± 5 s, P = 0.0.39) and in cold pressor tolerance after cumulative doses of 16 mg (18 ± 24 s, P = 0.018) and 32 mg (48 ± 73 s, P = 0.041) IV hydromorphone; cold pressor tolerance scores were not significant for 16 mg (1 ± 15 s, P = 0.619) or 32 mg (7 ± 16 s, P = 0.066) buprenorphine. Hydromorphone and buprenorphine compared with placebo showed greater ratings on subjective measures of high, any drug effects, good effects, and drug liking . Adverse events were more frequent during the hydromorphone compared with buprenorphine and placebo conditions for nausea, pruritus, sedation, and vomiting. Conclusions: In this acute clinical pain model, high doses of IV hydromorphone (16 to 32 mg) were most effective in achieving analgesia but also displayed higher abuse liability and more frequent adverse events. Cold pressor testing was the most consistent measure of opioid-related analgesia. Abstract : Large doses of intravenous hydromorphone can provide analgesia in buprenorphine-maintained individuals. However, the use of hydromorphone for analgesia in buprenorphine-maintained individuals confers greater abuse liability and side effects than does supplemental intravenous buprenorphine.